Modified screen-printed electrode for the FIA-amperometric determination of 2-nitro-p-phenylenediamine - Huayhuas-Chipana, Bryan C. [UNESP]; Foguel, Marcos Vinicius [UNESP]; Gonçalves, Luís Moreira; Sotomayor, Maria D.P.T. [UNESP] (Elsevier, 2017)
This work presents the development of a modified sensor coupled to a flow injection analysis (FIA) system for the determination of 2-nitro-p-phenylenediamine, an important compound in hair dyes. To achieve this, a commercial screen-printed gold electrode (SPAuE) previously electrochemically treated to become nanostructured, was covered with a self-assembled monolayer (SAM) of 3-mercapto-1-propanesulfonate (MPS) and, subsequently, was covered by multilayers of chitosan, sodium dodecyl sulphonate (SDS) and nickel(II) phthalocyanine-tetrasulfonic acid (NiPcTs) in a layer-by-layer technique to improve the sensor's sensibility. The analytical response of the proposed methodology was evaluated in batch by square wave voltammetry (SWV) and by amperometry coupled to a FIA system, with limits of detection of 1.2 and 1.6 μmol L− 1, respectively.
Keywords: 2-Nitro-p-phenylenediamine; Electroanalysis; Electrochemical sensor; Electrochemistry; Flow analysis; Microfluidics